1985
DOI: 10.1002/tera.1420320203
|View full text |Cite
|
Sign up to set email alerts
|

Two massive congenital intracranial immature teratomas with neck extension

Abstract: In this report we detail two congenital intracranial immature teratomas, noteworthy for their massive intracranial growth and extension through the skull with compromise of neck structures. Cytogenetic studies were done in both cases on the fetuses and their tumors and are the first in the literature. Few previously reported congenital intracranial teratomas have been described with neck extension. In both cases, polyhydramnios was detected by prenatal ultrasonography and was possibly caused by the laryngoesop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 11 publications
0
9
1
2
Order By: Relevance
“…Isochromosome 12p is well known in testicular germ cell tumors (Rodriguez et al, 1992). T h r e e congenital immature teratomas of the brain have been karyotyped so far, but i(12p) was not observed in anv of the three (Hecht et al, 1984;Rostad et al, 1985). However, trisomy 12 was found in our case.…”
Section: Discussioncontrasting
confidence: 79%
“…Isochromosome 12p is well known in testicular germ cell tumors (Rodriguez et al, 1992). T h r e e congenital immature teratomas of the brain have been karyotyped so far, but i(12p) was not observed in anv of the three (Hecht et al, 1984;Rostad et al, 1985). However, trisomy 12 was found in our case.…”
Section: Discussioncontrasting
confidence: 79%
“…Chromosomal analyses were performed in 17 cases, most of them after amniocentesis [7]. Only 3 of these teratomas had a pathologic karyotype affecting both fetus and tumour [3,11,16], while in 5 studies a normal diploid karyotype was found in fetus and tumour [1,5,12,13,17]. In the remaining 9 cases karyotyping was performed on the fetus but not on tumour material [7].…”
Section: Discussionmentioning
confidence: 99%
“…Routine ultrasound examination during pregnancy allows for the early antenatal detection of teratomas. Ultrasound imaging is well suited to the diagnosis of intracranial teratomas in utero because of its ability to detect features such as calcifications, multicystic components, cranial enlargement, gross distortion of normal cerebral architecture by a hyperechoic, multicystic mass, and polyhydramnios 9,10 . The prenatal diagnosis of teratomas is important for timely counseling of the parents and as an aid in obstetric decisionmaking.…”
Section: Prenatally Detected Congenital Orbital Teratomamentioning
confidence: 99%